ICT and productivity growth within value chains - Chuan Liu; Marianne Saam (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
To what extent have economies become better off because of the diffusion of information and communication technologies (ICT)? We analyze this question based on a growth accounting approach at the level of final output. This approach traces productivity improvements not within sectors but within value chains. It allows judging in a better way to what extent more or better products have become available to final users, in particular consumers, as a result of the diffusion of ICT. A main result is that more than half of the productivity gains related to ICT capital deepening for manufactured goods are contributed by upstream industries. The major part of this contribution is domestic rather than foreign. Moreover, the high sectoral growth in total factor productivity (TFP) in the ICT sector contributes only moderately to TFP growth in non-ICT value chains via the use of intermediates. – – Wie hat die Verbreitung von Informations- und Kommunikationstechnologien (IKT) den Wohlstand in Volkswirtschaften erhöht? Wir untersuchen diese Frage basierend auf einem Growth-Accounting-Ansatz auf der Ebene von Endprodukten. Dieser Ansatz betrachtet Produktivitätssteigerungen nicht innerhalb von Sektoren, sondern innerhalb von Wertschöpfungsketten. Er ermöglicht es besser zu beurteilen, inwieweit die Menge oder Qualität von Produkten für Endverbraucher, insbesondere für Konsumenten, dank der Diffusion von IKT zugenommen hat. Ein zentrales Ergebnis ist, dass mehr als die Hälfte der Produktivitätssteigerungen, die durch eine Zunahme der IKT-Kapitaltiefe bei der Fertigung von Gütern erfolgen, von IKT-Investitionen auf Vorleistungsstufen beigetragen wird. Der Großteil dieses Beitrags entsteht im Inland. Weiterhin trägt das hohe Wachstum der totalen Faktorproduktivität (TFP) im IKT-Sektor über die Nutzung von Zwischengütern nur moderat zum TFP-Wachstum in Wertschöpfungsketten von Nicht-IKT-Produkten bei.
Keywords: E22; F62; O47; 330; ICT; economic growth; productivity; value chains; growth accounting